Ecological health assessment of riparian zone of Yangtze River based on trapezoid cloud model in Jiangsu Province, China - Yangyang Lu; Gongxian Fang; Mingjiang Deng; Guohua Fang; Zihan Zhu; Changran Sun; Zitong Yang (Ecological Indicators)
In recent years, the ecological service functions of riparian zones have been destroyed owing to human activities. To perform scientific territorial spatial planning and ecological restoration of the riparian zone, there is an urgent need to develop a targeted evaluation index system and method for riparian zone ecological health. By analyzing the relationship between the riparian zone ecological health, river ecosystems, and human social well-being, the ecological health connotation of the riparian zone was analyzed, and an evaluation index system of riparian ecological health was established based on the pressure-state-response model. To address the problems of randomness and fuzziness in the riparian ecological health assessment process, a riparian ecological health assessment model based on the trapezoid cloud model was established by combining the weights obtained from the improved order relation analysis method with the degree of index certainty obtained from the trapezoid cloud model. The riparian zone of the Yangtze River in Jiangsu Province, China, was selected for the evaluation and analysis. The results show that: (1) the ecological health of the riparian zone in the study area was affected by multiple stress factors, such as urban expansion, port and industrial layout, and agricultural cultivation; however, the land-use change pressure was alleviated in the past 10 years; (2) compared with the traditional order relation method and cloud model, the combination of the improved order relation analysis method and trapezoid cloud model showed higher rationality and applicability; and (3) according to the evaluation results, PEH, SEH, REH, and EH in the study area showed a significant improvement trend from 2013 to 2023. The regions rated as “Weak” and “ Relatively Weak” are mainly concentrated in the areas along the Yangtze River, such as Nanjing, Zhenjiang and Yangzhou, and the areas around the Yangtze River estuary. These regions face greater ecological pressure owing to intensive heavy chemical industries, and there is an urgent need to develop corresponding ecological management and restoration countermeasures.